The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1016/s0014-5793(97)00671-6
|View full text |Cite
|
Sign up to set email alerts
|

β‐Adrenergic stimulation of interleukin‐1α and interleukin‐6 expression in mouse brown adipocytes

Abstract: Mouse brown adipocytes in primary culture were shown to contain high levels of mRNA for interleukin-la (IL-la) which could be further stimulated up to 9-fold by norepinephrine (NE). Even higher stimulation by NE, up to 40-fold, was found in case of interleukin-6 (IL-6). Time-course of activation of both genes was biphasic, but the response of IL-6 gene was slower than of IL-la gene. IL-la mRNA level reached the maximum after 1 h and the second, lower increase, occurred after 8 h. IL-6 mRNA level showed first m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 21 publications
5
60
0
2
Order By: Relevance
“…Activation of β 2 ARs on cells in the periphery (Frost et al 2004) or central nervous system (Maimone et al 1993) promotes the synthesis and release of IL-6. Additionally, activation of β 3 ARs on adipocytes stimulates IL-6 transcription (Burysek and Houstek 1997). We have extended these findings in a recent study showing that systemic COMT inhibition increases circulating plasma levels of TNFα, IL-1β, and IL-6 in rat in a β 2 -and β 3 AR-dependent manner (Nackley et al 2005b).…”
Section: Potential Signaling Mechanisms Whereby β 2/3 Receptors Mediasupporting
confidence: 72%
See 1 more Smart Citation
“…Activation of β 2 ARs on cells in the periphery (Frost et al 2004) or central nervous system (Maimone et al 1993) promotes the synthesis and release of IL-6. Additionally, activation of β 3 ARs on adipocytes stimulates IL-6 transcription (Burysek and Houstek 1997). We have extended these findings in a recent study showing that systemic COMT inhibition increases circulating plasma levels of TNFα, IL-1β, and IL-6 in rat in a β 2 -and β 3 AR-dependent manner (Nackley et al 2005b).…”
Section: Potential Signaling Mechanisms Whereby β 2/3 Receptors Mediasupporting
confidence: 72%
“…Within recent years it has become increasingly recognized that proinflammatory mediators, including cytokines (e.g., TNFα, IL-1β, and IL-6), prostaglandins, and reactive oxygen species, also play an important role in mediating pain sensitivity (Burysek and Houstek 1997;Kress 2004;Maimone et al 1993;Marchand et al 2005;Sommer and Kress 2004). Activation of β 2 ARs on cells in the periphery (Frost et al 2004) or central nervous system (Maimone et al 1993) promotes the synthesis and release of IL-6.…”
Section: Potential Signaling Mechanisms Whereby β 2/3 Receptors Mediamentioning
confidence: 99%
“…it should be noted that Burysek et al 25 reported an up to 40-fold increase of IL-6 in brown adipocytes stimulated with norepinephrine, a main inducer of thermogenesis. The authors of this article speculated that IL-6 produced by brown adipose tissue could play a paracrine role in the regulation of thermogenesis in this tissue.…”
Section: Rega Et Al Vegf Regulation By Cytokines In Adipose Tissuementioning
confidence: 94%
“…In addition to these cells, several tissues including BAT also produce IL-1a. 38) As described above, the receptor of this cytokine exists on the surface of brown adipocytes, and is regulated in response to cold stimulation. 38) In addition, it is also observed that cold stimulation decreases expression of the IL-1a gene.…”
Section: Fig 2 Transcription Factors That Bind To Enhancer Region Omentioning
confidence: 97%
“…The interleukin-1 type I receptor (IL-1RtI) exists on the surface of brown adipocytes. 38) IL1RtI acts as the receptor of interleukin-1a (IL-1a) and IL1b, known as pyrogens secreted from leukocytes. 39) IL1b has the potential to activate thermogenesis.…”
Section: Genes Whose Expression Is Changed In Re-sponse To Activationmentioning
confidence: 99%